Effect of premolar extraction on Bolton overall ratio in north Indian population - Ankit Garg; Sushil Kumar; Munish Reddy; Namita Jaggi; Anshul Singhal; Saeed Bin Hamid; Abhishek Singha Roy (International Journal of Medical Research and Review, 2016)
Introduction: Bolton ratio is considered as seventh key of normal occlusion. Many orthodontic patients have to undergo premolar extractions as a part of treatment.Aims and objectives: The present study was taken up to investigate the effect of premolar extractions on Bolton’s overall ratios in a sample of north Indian population.Materials and methods: Mesiodistal tooth widths were measured on pretreatment dental casts of 200 subjects (100 males and 100 females). The Bolton’s overall ratios were determined before and after hypothetical premolar extractions and the subjects were divided into small, normal, and large overall ratio groups categorized by the Bolton standard deviation definition. Extractions were performed in the following combinations: (1) all first premolars, (2) all second premolars, (3) maxillary first and mandibular second premolars, and (4) maxillary second and mandibular first premolars.Results: The overall ratios decreased in every group after extraction of any combination of premolars. Maximum discrepancy was observed in the extraction of all first premolars and least in second premolars. Statistically significant differences were seen in the extraction pattern amongst males and females.Conclusions: In cases which require premolar extractions, it is mandatory to check if any discrepancy exists between different extraction patterns since the ratios may shift from normal to abnormal or vice versa as it may affect the interdigitation of teeth.